IMPROVING STUDENTS' SPEAKING ABILITY USING RADIO TALK SHOW PROGRAMME - Dewi Satria Elmiana (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
Media provide students and teachers with creative as well as practical ideas and enable them to meet various interests and needs, hence, this study analysed the implementation of using media particularly radio programme to improve students’ speaking ability. This study employed descriptive qualitative approach and there were 42 students of senior high school involved in this study. The results indicate that the implementation of media (radio talk show programme) assists students to improve their speaking ability; it can be one of methods in teaching and learning process especially in speaking class; and the influence of media (radio talk show programme) could encourages and motivates students to pull out their best of communication skill particularly in using English.